PENGUKURAN KEMISKINAN DI KABUPATEN BANYUMAS - Zaula Rizqi Atika; Ali Rokhman; Muslih Faozanuddin (Jurnal Sosial Soedirman, 2018)
The problems that arise in this research is how the measurement of poverty used in Banyumas. This study aims to determine the accuracy of the measurement of poverty used in Banyumas Regency. Dutta and Kumar (2013: 496) consider that a poverty measure needs to be associated with the ownership of physical assets and human assets. Physical assets may include ownership of household facilities, types of houses, sources of drinking water, toilet facilities, cooking fuel, productive assets and natural assets. Human assets consist of educational history, existence, and health of pregnant/ breastfeeding and the health status of household members against chronic diseases. The study was conducted with a qualitative approach. Informant selection techniques used in the study was purposive. Location of the study conducted at BPS (Central Statistics Agency), Dinsosnakertrans (Social, Employment and Transmigration Services) and Bapermas-PKB (Agencies of Community Development, Women and Family Planning) of Banyumas Regency. The results showed that the measurement of poverty versions of the Central Statistics Agency (BPS) is considered the most appropriate and closer to the reality in Banyumas based aspects of the ownership of physical assets and human assets. The results of poverty measurement BPS micro covers almost entirely of six sub-aspects of physical assets including ownership of household facilities, types of houses that are owned, use drinking water source of household, type of toilet that is owned, cooking fuel used and the ownership of natural assets, except ownership productive assets, while three sub-aspects of human assets entirely covers education history owned by a household, the existence, and health of pregnant and lactating women, the health status of household members to complete the chronic disease have on the measurement of micro BPS poverty.